Causal relationship between linoleic acid and type 2 diabetes and glycemic traits: a bidirectional Mendelian randomization study - Liang, Hao; Mu, Hai-Bo; Zhang, Fei-Hu; Li, Wen-Qiang; Li, Guo-Chen; Li, Wen-Dong; Liang, Min; He, Zeng-Lin (Frontiers in Endocrinology, 2023)
Objective: To investigate the causal relationships between linoleic acid and type 2 diabetes, and between linoleic acid and glycemic traits in European populations.Methods: This study employed a two-sample Mendelian randomization approach to infer causality between linoleic acid and type 2 diabetes, as well as between linoleic acid and glycemic traits, leveraging genetic variations. Data were sourced from genome-wide association study summary datasets. Random-effects inverse-variance weighted, weighted median, and MR-Egger methods were used for the two-sample Mendelian randomization analyses. Results were presented as odds ratios with a 95% confidence interval. Multiple sensitivity analyses were conducted to assess result robustness.Results:MR findings indicated a correlation between linoleic acid levels and the risk of type 2 diabetes, fasting blood glucose, and glycated hemoglobin(HbA1c), but not with fasting insulin. Specifically:type 2 diabetes (OR: 0.811, 95% CI: 0.688–0.956, P=0.013<0.05),fasting blood glucose (β_IVW): -0.056, 95% CI: (-0.091,-0.021), P=0.002 < 0.0125),glycated hemoglobin (β_IVW: -0.032, 95% CI: (-0.048,-0.015), P=0.0002 < 0.0125) and Fasting insulin (β_IVW: -0.024, 95% CI: (-0.056,-0.008), P=0.136 >0.05).Reverse MR analyses showed a correlation between type 2 diabetes and reduced levels of linoleic acid (β_IVW: -0.033, 95% CI: (-0.059,-0.006), P=0.014<0.05). Multiple sensitivity analyses also detected study heterogeneity but found no evidence of horizontal pleiotropy.Conclusion:High levels linoleic acid can reduce the risk of type 2 diabetes, fasting blood glucose, and glycated hemoglobin, but has no significant relation with fasting insulin. Type 2 diabetes can lower linoleic acid levels; however, no significant causal relationship was observed between the three glycemic traits and reduced levels of linoleic acid.